Deteksi Level Antibodi Pada Serum Darah Anjing Kintamani Pasca Vaksinasi Rabies dengan Direct ELISA - Cahyana, I Putu Agus Tirta; Pharmawati, Made; Narayani, Inna (Metamorfosa: Journal of Biological Sciences; Vol 8 No 1 (2021), 2021)
The success of rabies vaccination is characterized by the growth of seropositive antibody titers (?0.5 IU) after vaccination. One of the tests conducted to monitor antibody growth is ELISA (Enzyme Linked Immunosorbent Assay). This study aimed to determine the effect of different vaccine doses on the growth of rabies antibodies in kintamani dogs. The study was conducted using an experimental method with a study design using 2 variables, namely the difference in vaccine doses (0.5 and 0.75 cc) and the times of blood collection (1, 2 and 3 months after vaccination). Each vaccine dose was given to three kintamani dogs. Antibodies were measured using ELISA and data were analyzed with paired sample t-test between the treatment dose of 0.75 cc and 0.5 cc at months 1.2 and 3 after vaccination. The results showed that at first month the antibody titer were 2,12 IU at a dose of 0.75 cc and 3.72 IU at a dose of 0.5 cc. At second months, antibody titers were 7.74 IU (0.75 cc dose) and 10.85 IU (0.5 cc dose), while at third month, antibody titers were 5.73 IU (0.75 cc) and 9.00 IU (0.5 cc). Vaccine doses administered produce antibody titer levels that did not differ significantly between 0.75 cc and 0.5 cc doses.   Keyword : Antibody, ELISA, Kintamani Dog, Rabies